A Game Theoretic Approach for Efficient Resource Allocation in 5G Networks - Aspasia Koukouvela; Christos Bouras; Vasileios Kokkinos; Apostolos Gkamas; Philippos Pouyioutas (The 14th International Congress on Ultra Modern Telecommunications and Control Systes (ICUMT 2022), October 11 – 13, 2022, Valencia, Spain, 2022)
Heterogeneous Networks (HetNets) have been lauded as a key technology for 5G communications, enabling fast growth in mobile traffic. HetNets may also expand the network’s capacity and serve more users. However, interference between small cells and macro-cells makes Quality of Service (QoS) more difficult to achieve, and thus novel protocols, new technologies, and future trends should also be included in order to provide efficiency in Resource Allocation (RA). Game Theory (GT) concepts have been widely used in a variety of engineering design challenges in which one component’s activity affects and perhaps conflicts with the actions of other components. As a result, game formulations are utilized, and the idea of equilibrium is applied to find a stable solution for the participants. In this paper, we compare two algorithms used for RA, the first being a classical RA algorithm and the second being a game theoretic one. The game implemented is called “Tragedy of the Commons”, and is applied in a non-cooperative network.